The Relationship Between Learning Discipline and Learning Achievement Students in Civics Subjects - Loriana Pabalik; Nani Mediatati; Yosaphat Haris Nusarastriya (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
This study aims to determine the relationship (correlation) between student learning discipline and student learning achievement in Civics subject in class X SMK Negeri 2 Salatiga. The samples in this study were students of class X TKJ B and X DPIB B who were taken by nonrandom sampling, a total of 70 students. The data collection techniques used questionnaires and documentation. The data analysis technique uses the Product Moment correlation statistical test from Person. Based on the results of the statistical correlation test, it shows that there is a significant positive correlation between learning discipline and Civics learning achievement of class X students of SMK Negeri 2 Salatiga. The results of the correlation analysis (test) between the learning discipline variable and student learning achievement show a positive correlation of r = 0. 302 with a significant level of 0.011 <0.05. With this positive correlation result is shows that learning achievement is not entirely influenced by learning discipline factors, but also influenced by factors outside the learning discipline. Although the contribution (contribution) of learning discipline to learning achievement is small, the habit of learning discipline must still be instilled in students.